2008
DOI: 10.1097/ta.0b013e3181878028
|View full text |Cite
|
Sign up to set email alerts
|

An FFP:PRBC Transfusion Ratio ≥1:1.5 Is Associated With A Lower Risk Of Mortality After Massive Transfusion

Abstract: In patients requiring >/=8 units of blood after serious blunt injury, an FFP:PRBC transfusion ratio >/=1:1.5 was associated with a significant lower risk of mortality but a higher risk of acute respiratory distress syndrome. The mortality risk reduction was most relevant to mortality within the first 48 hours from the time of injury. These results suggest that the mortality risk associated with an FFP:PRBC ratio <1:1.5 may occur early, possibly secondary to ongoing coagulopathy and hemorrhage. This analysis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
233
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(245 citation statements)
references
References 22 publications
5
233
1
6
Order By: Relevance
“…Wafaisade et al (29) found that the survival rate improves significantly in patients with a FFP:RBC ratio of >1:1. However, Sperry et al (16) found that the infusion of FFP and RBC improved the survival rate at a ratio of 1:1.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wafaisade et al (29) found that the survival rate improves significantly in patients with a FFP:RBC ratio of >1:1. However, Sperry et al (16) found that the infusion of FFP and RBC improved the survival rate at a ratio of 1:1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have demonstrated a survival benefit for bleeding trauma patients when transfused with an early high RBC:fresh frozen plasma (FFP) 1:1 ratio, in civilian as well as military settings (13)(14)(15)(16). To promote the clinical treatment of MT, the present study aimed to explore the effective blood component transfusion ratio through a retrospective study of MT.…”
Section: Introductionmentioning
confidence: 99%
“…22 This area of debate is likely to continue until a prospective randomized trial is completed. 1,[4][5][6][7]9 Although the technique of perihepatic packing was founded in 1908 with Pringle's discussion of hepatic trauma, 43 the modern interpretation of this work occurred in the late 1970s, [44][45][46] followed by the concept of truncated operations with concurrent intra-abdominal packing for patients in physiologic extremis by Stone and colleagues in 1983. 47 This philosophy was then coined "damage control" by Rotondo and colleagues, given its obvious conceptual similarity to the Navy's use of the same term.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] While the effect on overall mortality in the civilian population is still debated, [21][22][23][24] massive resuscitations with high plasma:packed red blood cell (RBC) ratios remain promising for addressing the early coagulopathy 25 and acidosis frequently associated with life-threatening injury. 10 Additional benefits of a formal MTP include earlier administration of blood products during the resuscitation phase, improved overall efficiency, decreased total blood product use during a patient's hospital stay and a substantial economic savings.…”
mentioning
confidence: 99%
“…Clinical observations and scientific findings still recommend a hemostatic management during the early in-hospital resuscitation including the administration of a large number of blood products [7,8]. Several studies have shown a reduced mortality when pRBCs and FFPs were administered in a 1:1 ratio [9,10]. However, due to its significant influence towards complications, e.g.…”
Section: Introductionmentioning
confidence: 99%